1990
DOI: 10.1210/jcem-71-3-618
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Diagnosis and Treatment of Fetal Goitrous Hypothyroidism

Abstract: Newborn screening programs for the detection of congenital hypothyroidism have dramatically shortened the time before treatment is begun. However, concern still exists about central nervous system sequelae which may persist due to a period of untreated intrauterine hypothyroidism. Presence of polyhydramnios led to the ultrasound diagnosis of a fetal goiter. Hypothyroidism was confirmed at 34 weeks gestation by percutaneous fetal blood sampling, which revealed an elevated TSH (186 mU/L) and a low T4 (19.3 nmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…However, this is an invasive procedure, associated with 1% fetal loss (12). However, this approach allows the early diagnosis of fetal hypothyroidism and the provision of substitutive therapy in utero (25,26). Several recent studies have shown that intrauterine hypothyroidism is associated with decreased IQ values at 3-7 years even if a correct neonatal thyroid hormone replacement therapy is provided (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is an invasive procedure, associated with 1% fetal loss (12). However, this approach allows the early diagnosis of fetal hypothyroidism and the provision of substitutive therapy in utero (25,26). Several recent studies have shown that intrauterine hypothyroidism is associated with decreased IQ values at 3-7 years even if a correct neonatal thyroid hormone replacement therapy is provided (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large goiter may cause malpresentation and may complicate labor. Perelman et al 3 reported that fetal goitrous hypothyroidism was successfully treated by intraamniotic injection of 500 µg levothyroxine sodium every 10-14 days. Davidson et al 4 has also stated that weekly injections of 250 µg of levothyroxine would closely approximate the thyroxine requirement of a newborn baby with hypothyroidism (10 µg/kg body weight/day).…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal diagnosis of fetal goiter may be crucial for the immediate postnatal management of affected neonates. It has been reported that fetal goitrous hypothyroidism was diagnosed in utero based on sonography and on thyroid stimulating hormone (TSH) assays of umbilical blood samples and amniotic fluid, and was successfully treated by intra-amniotic injection of thyroid hormone, resulting in a decrease in fetal TSH level and a decrease in the size of the goiter [2][3][4][5] . Though the high vascularity of fetal goiter has been reported 6 the circulatory status of such fetuses has remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This explains why, even in congenital hypothyroidism with delayed bone maturation at diagnosis (indicating a prenatal onset), the intellectual outcome is typically normal if treatment is instituted shortly after birth [12,13]. Thus, in utero treatment of fetal hypothyroidism is usually only considered in rare circumstances, such as for goiters causing hydramnios or when vaginal delivery is likely to be impeded [14]. We have reported results from 12 cases that confirm the feasibility and safety of intrauterine L -thyroxine treatment of nonimmune fetal goitrous hypothyroidism.…”
Section: Fetal Hypothyroidismmentioning
confidence: 99%